Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi: (Studi di Kantor Pelayanan Pajak Pratama Surakarta) - Arif Sulistyo Wibowo; Siti Nurlaela; Yuli Chomsatu (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to determine the effect of tax awareness, tax sanctions, quality of tax services, tax socialization, tax knowledge and tax incentives on individual taxpayer compliance at KPP Pratama Surakarta. The population in this study were 81,001 individual taxpayers registered at the KPP Pratama Surakarta. Sampling using incidental sampling method as many as 100 respondents. Source of data is primary data through questionnaires. The data analysis technique used in this study used multiple linear regression analysis. The results of this study indicate that the quality of tax services and knowledge of taxation affect individual taxpayer compliance. Meanwhile, tax awareness, tax sanctions, tax socialization, and tax incentives have no effect on individual taxpayer compliance.